Species Composition and Some Biological Features of Scorpions in Kazerun District, Southern Iran - Mansour Nazari; Ali Najafi; Mohammad Reza Abai (Tehran University of Medical Sciences, 2018)
Background: Scorpions have medical importance in the studied area with 2377 cases of envenoming during past six years. This study was the first to explore the scorpion species and dispersion in the Kazerun District during 2014-2015. Methods: The studied sites were selected based on different topographic conditions such as plain, foothill and mountainous which formed four geographical zones with three villages in each zone. The sampling was carried out twice each month throughout the year. Daytime collections were carried out using hand digging tools for moving stones and excavate the borrows, as well as night sampling, is done with the black light device. The coordinate of locations was recorded with a GPS. The collected specimens were maintained in 70% ethanol and identified using authorized keys. Results: Overall, 800 scorpions were sampled from different parts of Kazerun District, bringing the species richness to 9 belonged to 3 families of Buthidae, Scorpionidae, and Hemiscorpionidae. The Mesobuthus eupeus (84.6%) was prominent vice versa M. caucasicus (0.1%) had lowest abundance. Other species comprised Compsobuthus matthiesseni (5.3%), Androctonus crassicauda (5.0%), Razianus zarudnyi (2.0%), Hemiscorpius lepturus (1.5%), Orthochirus sp (0.9%), Hottentotta zagrosensis (0.4%), and Scorpio maurus (0.3%). The seasonal activity of the scorpions showed a lower peak in Mar, with the main peaks in Aug for the dominant species. Mesobuthus caucasicus is recorded for the first time in the Fars Province, southern Iran. Conclusion: All the known dangerous scorpions, including H. lepturus, M. eupeus and A. crassicauda were revealed in the studied area.